(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2025)
By studying international conflicts, we can see that they have two distinct dimensions: the first is the negative dimension, and the second is the positive dimension in conflicts that reach the point of confrontation. Conflicts are an inevitable issue in the context of international relations, and they have been and still are, and will remain so despite all theoretical attempts that seek to limit or reduce them. All of this enables us to know the most prominent basic characteristics that distinguish the phenomenon of the use of force in international relations, the most important of which is the use of hard (military) force in conflicts, and with the vast technological developments that have enabled countries and powers to use other forms of force in wars and conflicts when interests conflict between countries that always seek to achieve the interests of certain countries through their foreign policy, and all of this is linked to global politics and international conflict. Thus, the first and basic goal of using hard power, or the types of power that have emerged in the history of conflicts of all kinds in foreign policy, is to maintain superiority and prevent other countries from competing. The best strategy for a state is to always be strong by possessing hard power (military) as well as other forms of power and its tools, and striving to increase it, although military power remains a priority in addition to everything related to it, the most important elements of power. All major historical changes in international conflicts and disputes have only occurred through possessing hard power, or threatening force, or actually using it.